2024
DOI: 10.1038/s41598-024-52397-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis identifies coagulation factor II receptor as a potential biomarker in stomach adenocarcinoma

Xingwei Wu,
Shengnan Wang,
Chenci Wang
et al.

Abstract: Coagulation factor 2 thrombin receptor (F2R), a member of the G protein-coupled receptor family, plays an important role in regulating blood clotting through protein hydrolytic cleavage mediated receptor activation. However, the underlying biological mechanisms by which F2R affects the development of gastric adenocarcinoma are not fully understood. This study aimed to systematically analyze the role of F2R in gastric adenocarcinoma. Stomach adenocarcinoma (STAD)-related gene microarray data and corresponding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…F2R expression is upregulated in smooth muscle actin-positive breast fibroblasts surrounding carcinoma cells [28] and in activated fibroblasts in arteries and veins [29] An increase in F2R has been reported in various GI tumors including cholangiocarcinoma, colon adenocarcinoma, esophageal carcinoma, rectum adenocarcinoma, and in stomach adenocarcinoma, where higher F2R expression was associated with infiltration of a number of immune cell populations including CD4+ lymphocytes, macrophages, and eosinophils. F2R silencing via siRNA transfection studies demonstrated that F2R promoted stomach adenocarcinoma cell proliferation, migration, and invasion [30]. Interestingly, our analysis identified an upregulation in mast cell to fibroblast (CTSG_F2R) and lymphocyte to fibroblast (PRSS3-F2R) signaling in active vs. remission EoE.…”
Section: Discussionmentioning
confidence: 62%
“…F2R expression is upregulated in smooth muscle actin-positive breast fibroblasts surrounding carcinoma cells [28] and in activated fibroblasts in arteries and veins [29] An increase in F2R has been reported in various GI tumors including cholangiocarcinoma, colon adenocarcinoma, esophageal carcinoma, rectum adenocarcinoma, and in stomach adenocarcinoma, where higher F2R expression was associated with infiltration of a number of immune cell populations including CD4+ lymphocytes, macrophages, and eosinophils. F2R silencing via siRNA transfection studies demonstrated that F2R promoted stomach adenocarcinoma cell proliferation, migration, and invasion [30]. Interestingly, our analysis identified an upregulation in mast cell to fibroblast (CTSG_F2R) and lymphocyte to fibroblast (PRSS3-F2R) signaling in active vs. remission EoE.…”
Section: Discussionmentioning
confidence: 62%